Alvar Aalto in Yyteri: Naturecultural quest for organic land use planning in the City of Pori, Finland - Hiedanpää Juha (Cultural Science)
Alvar Aalto’s regional plan for the Kokemäenjoki river valley (1943) became a naturecultural plan of its time. In his planning approach, Aalto blurred the boundary between nature and culture. Aalto emphasised the everyday nature of human activities and the organicity and rhythm of the landscape. I will think with one area – Yyterinniemi – at the mouth of the Kokemäenjoki river about the effects and timeliness of Aalto’s planning approach. I will discuss how the organic complexity, unity and dynamic patterns of doing and undergoing are indeed present in Yyterinniemi, and how the city of Pori, local landowners and other actors have tried to, spontaneously and intentionally, maintain and develop Yyterinniemi as a multispecies assemblage and enable it to fulfil its short-term functions and long-term coevolutionary potential.